Progestogen only contraception in women with congenital heart disease - Francesc Baró-Mariné; Antonia Pijuan-Domènech; Maria del Mar Goya; Elena Suárez-Edo; Berta Miranda-Barrio; Laura Dos-Subirà; Maria Luisa Pancorbo; Ignacio Ferreira-Gonzalez; Elena Carreras-Moratonas (Journal of Obstetrics and Gynaecology, 2024)
Background There is little information of progestogen-only contraceptives in patients with congenital heart disease (CHD) on the long-term.Objective To evaluate the use of contraception in patients with CHD. We studied both short-acting reversible contraceptives (SARCs), oral progestin-only pills (POPs) and long-acting reversible contraceptives (LARCs): intrauterine devices (IUD-IPs) and subdermal implants both impregnated with progestogens (SI-IPs).Study design Retrospective study of all women attending the preconception clinic. Contraceptive methods were classified in three TIERs of effectiveness before and after consultation. ESC classification regarding pregnancy risk, WHOMEC classification for combined oral contraceptive safety was collected.Results Six hundred and fifty-three patients. A significant proportion of them switched from TIER 3 to TIER 2 or 1 (p < .001) after consultation. One hundred and ninety-nine patients used POPs, 53 underwent IUD-IPs implantation and 36 SI-IPs, mean duration was 58 ± 8, 59 ± 8 and 53 ± 38 months, respectively.Conclusions Because of their safety and efficacy, IUD-IPs and SI-IPs should be considered as first-line contraception in patients with CHD.